Comparison of low and high Sodium and Potassium content in ORS by Flame Emission Spectroscopy - Farin Banu,; Kuldeep Wathra,; Ranu Sharma,; Maya Sharma,; Ankit Paliwal, (Asian Journal of Pharmaceutical Research and Development, 2026)
A study was carried out to determine the content of Na and K in two different brands of ORS powder by Flame photometric method. The Na content was found to be higher in Govt. supplied sample and K content was higher in the private sample. A study was conducted to compare sodium and potassium content in various ORS powder brands using Flame Photometry (Atomic Emission Spectroscopy), revealing variations in cation concentration compared to standard requirements. Results indicated that while most samples met specifications, some brands showed significant variance in sodium/potassium levels. Flame photometry proved to be a simple, quick, and accurate method for this quantitative analysis. Oral Rehydration Solution (ORS) is widely used for the treatment of dehydration caused by diarrhoea, cholera, and gastroenteritis. Sodium and potassium are the major electrolytes present in ORS and play an important role in maintaining fluid and electrolyte balance in the body. Accurate estimation of these ions is necessary because excess or deficiency may lead to complications such as hypernatremia, hyponatremia, hyperkalaemia. Flame Emission Spectroscopy (Flame Photometry) is a rapid, simple, and sensitive analytical technique commonly used for the determination of sodium and potassium in ORS formulations. This review paper compares low and high sodium-potassium content in various ORS formulations using flame emission spectroscopy and discusses the principle, methodology, advantages, and analytical significance of the technique. Studies reveal that flame photometry provides accurate and reliable estimation of electrolyte concentration in commercial ORS powders and solutions.